2005
DOI: 10.1016/j.amjhyper.2004.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced changes in ?-adrenergic response: An experimental study in the isolated rat papillary muscle

Abstract: Our results suggest that the insulin-induced modulation of contractility is calcium independent and insulin leads to a supersensitization on the beta(1)-adrenoceptors without effects on beta-adrenoceptor independent adenylate cyclase-related pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recent experimental results from our lab as well as others depicted a direct positive inotropic effect of insulin on both normal and simulated I/R cardiomyocytes [20,21]. However, existing data concerning the functional effects of insulin on the myocardial response to b-AR activation are quite limited and inconsistent [30][31][32].…”
Section: Discussionmentioning
confidence: 86%
“…Recent experimental results from our lab as well as others depicted a direct positive inotropic effect of insulin on both normal and simulated I/R cardiomyocytes [20,21]. However, existing data concerning the functional effects of insulin on the myocardial response to b-AR activation are quite limited and inconsistent [30][31][32].…”
Section: Discussionmentioning
confidence: 86%
“…[12][13][14] Insulin's inotropic effect may be related to enhanced ␤-adrenoreceptor sensitivity as well as improved calcium handling properties of the myocyte. 15,16 T3 acts on the myocyte directly and indirectly and by genomic and nongenomic mechanisms. 17,18 It is able to lower vascular resistance 7,19 and have positive effects on the adrenoreceptor and calcium handling properties of the myocyte.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insulin might modulate the inotropic response of ␤-adrenergic receptor agonists in mammalian hearts. A low concentration of insulin (0.3 nmol/liter) sensitized the positive inotropy of isoproterenol in the isolated rat papillary muscle, 33 but a high concentration (6 mol/liter) impaired the inotropic effect of norepinephrine in cat papillary muscle. 10 Baltensperger et al 34 showed that insulin is able to stimulate insulin receptor-catalyzed phosphorylation of the ␤ 2 -adrenergic receptor.…”
Section: Discussionmentioning
confidence: 98%